CONSUMER ATTITUDE MEASUREMENT TOWARDS ONLINE SHOPPING - Nia Lefiani; Anggalia Wibasuri; Ketut Sardoni; Yuliasari Yuliasari (Proceeding International Conference on Information Technology and Business, 2019)
The study is aimed at testing the effect of Perceived Ease Of Use (PEU), Perceived Usefulness (PU), Customer Experience (CE) and Website Image (WI) effect on the Attitude to Use (AU) on Online Shopping (OS) in Indonesia. This type of research is Causal Associative research. Sampling in this study uses a purposive sampling technique with a sample size of 100 respondents taken using the Slovin formula. The data analysis method in this study uses the Partial Least Square (PLS) method. The design of this hypothesis among others Perceived ease of use (PEU) impact positively on Attitude to Use (AU), the Perceived usefulness (PU) impact positively on the Attitude to Use (AU), Customer Experience (CE) effect positive to Attitude to Use (AU), web Image (WI) impact positively on the Attitude to Use (AU).Keywords: Perceived Ease of Use (PEU), Perceived Usefulness (PU), Customer Experience, Website Image and Attitude to Use.